2022
DOI: 10.3390/designs6050081
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric Measurement of Thai Older Farmers for Agricultural Tools and Workplace Design

Abstract: Agricultural workers usually perform most occupational operations manually. Mismatch between farmers’ anthropometric dimensions and tools or equipment are known to be contributing factors related discomfort, fatigue, injuries, and biomechanical stress to the users, especially for older farmers. A cross-sectional survey was carried out on 197 male and 284 female older farmers in Nong Suea District, Pathum Thani Province, Thailand. The convenience sampling method was used to select the subjects. Thirty-three ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Males' hands were 82.0 mm wide and females' hands were 72.5 mm wide. Kaewdok et al [20] in their studies in 2022 on a Thai population revealed that the average hand length was 182.0 mm for males and 170.0 mm for females. And hand breath was 87.0 mm for males and 81.0 mm for females.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Males' hands were 82.0 mm wide and females' hands were 72.5 mm wide. Kaewdok et al [20] in their studies in 2022 on a Thai population revealed that the average hand length was 182.0 mm for males and 170.0 mm for females. And hand breath was 87.0 mm for males and 81.0 mm for females.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Because most fruits, such as grapes, need to strictly control the yield in the planting process to ensure quality and income, their output should be measured at least from both yield and output value, and so it is more suitable to choose DEA to measure the technical efficiency of grape growers . Since this paper focuses on the impact of factor input (especially labor factor input) on output [67][68][69][70][71], it adopts an input-oriented variable model of returns to scale, namely the BCC model. Table 1 shows the input and output indicators of computational technical efficiency.…”
Section: Input-output Modelmentioning
confidence: 99%
“…Studies such as [ 16 ] have focused on addressing the mismatch of workplace height for manual handling, utilizing female anthropometric measures to reduce musculoskeletal disorders. The design of manual tools for various occupations, including farming [ 17 ], hand looming [ 18 ], dentistry [ 19 ], and packaging [ 20 ], has integrated women’s anthropometry to mitigate fatigue and biomechanical stresses. Furthermore, the application of anthropometric measurements extends beyond civilian occupations to active duty, where studies [ 21 , 22 , 23 , 24 ] have utilized female anthropometric data to design ergonomic body armor tailored to their body measurements, enhancing battlefield operational performance.…”
Section: Introductionmentioning
confidence: 99%